A foam ceramic building block and its preparation method and use method

By using raw materials such as tap water tail mud, aluminum ash, flue ash, etc., combined with pore-forming agents such as boron mud, calcium carbide slag and fillers such as pine nuts, control stress and component ratios, the problem of poor performance of existing foam ceramic materials is solved, and foam ceramic blocks with high strength and good thermal insulation performance are achieved. They are suitable as indoor partition materials and have the characteristics of low cost and industrialization.

CN116903389BActive Publication Date: 2025-03-18THE THIRD CONSTR OF CHINA CONSTR EIGHTH ENG BUREAU
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310888363.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-19
Publication Date
2025-03-18
Estimated Expiration
2043-07-19

AI Technical Summary

Technical Problem

The insulation, strength and other properties of existing foam ceramic materials are not ideal and need to be further improved.

Method used

The main raw materials are used for tap water tail mud, aluminum ash, flue ash and sulfuric acid slag, boron mud, calcium carbide slag, and industrial salt mud are pore-making agents, and pine nuts, castor beans, and croaker grass powder are fillers. By controlling the dosage and stress of each component, foam ceramic blocks with high strength and good thermal insulation properties are formed.

Benefits of technology

It improves the strength, insulation effect and sound absorption capacity of foam ceramic blocks, is suitable as an indoor partition material, and has a low production cost and has an industrial foundation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116903389B_ABST
    Figure CN116903389B_ABST
Patent Text Reader

Abstract

The present invention provides a foam ceramic building block and a preparation method and a use method thereof. The raw materials of the building block include: 100 parts of a main material, 5 to 20 parts of a pore-forming agent, and 5 to 10 parts of a filler. Tap water tail mud, aluminum ash, flue ash and sulfuric acid slag are ground into powder as the main material, at least one of boron mud, carbide slag and industrial salt mud is dried and ground into powder as a pore-forming agent, at least one of pine nuts, castor beans and Spartina alterniflora powder is crushed as a filler, the above raw materials are mixed to form embryos, calcined and cooled to obtain building blocks. The foam ceramic building blocks prepared by the present invention are adhered to each other by applying a masonry agent. The foam ceramic building block has the characteristics of strong mechanical properties, good thermal insulation effect and excellent sound absorption capacity, and is of great significance in the fields of improving the comprehensive utilization rate of solid waste and developing energy-saving building materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and further to the technical field of building blocks, in particular to a foam ceramic building block and a preparation method and a use method thereof. Background Art

[0002] With the rapid economic development and continuous improvement of production technology, the types and quantities of solid waste generated are also increasing year by year. Traditional treatment methods such as incineration and landfill not only occupy a large amount of land, but also pose a serious threat to the local ecological environment and the safety of life and property of residents. It is of great practical significance to explore the use of solid waste resources to serve economic construction.

[0003] Modern economic development has led to an increasing conflict between energy and the environment. Currently, building energy consumption accounts for about 30% of the world's total energy consumption, and CO2 emissions from building energy use account for 1 / 3 of the world's total emissions. By developing low-cost, environmentally friendly building energy-saving materials, energy consumption can be effectively reduced and carbon emissions can be reduced.

[0004] Foam ceramic material is a porous material with pore sizes ranging from nanometers to micrometers. Foam ceramic has a large number of interconnected and closed pores, and has the advantages of low density, low thermal shock resistance, low thermal conductivity, low dielectric constant, high temperature stability, etc. It can be widely used in catalysts, filtration, thermal insulation materials, biological transplant materials, etc.

[0005] However, the thermal insulation, strength and other properties of foam ceramic materials currently on the market are not ideal and need to be further improved. Summary of the invention

[0006] In view of the above-mentioned prior art, in order to improve the strength, thermal insulation and other effects of ceramic blocks, the present invention provides a foam ceramic block and a preparation method and a use method thereof.

[0007] The invention provides a foam ceramic building block, comprising the following raw materials in parts by weight: 100 parts of main material, 5-20 parts of pore formers, and 5-10 parts of fillers. The main material comprises 10-70 parts of tap water tailings, 10-30 parts of aluminum ash, 10-30 parts of flue ash, and 10-30 parts of sulfuric acid slag.

[0008] Preferably, the pore-forming agent is at least one of boron mud, carbide slag and industrial salt mud.

[0009] In the above technical scheme, the components in the boron mud, carbide slag and industrial salt mud will decompose when heated to generate volatile gases. At the same time, the boron mud, carbide slag and industrial salt mud react with MgO, aluminum oxide, iron oxide and other substances contained in the raw materials to generate aluminum hydroxide, magnesium hydroxide, iron hydroxide and other substances. These substances decompose when heated to produce water vapor evaporation to form pores. The above components synergistically improve the thermal insulation performance of the foam ceramic material. The foam ceramic material also needs to meet the strength requirements in industrial applications. Therefore, by controlling the dosage of the above components, the product has good thermal insulation performance and porosity while ensuring strength.

[0010] On the other hand, the sulfur-containing substances in the sulfuric acid slag react with the calcium-containing substances in the boron mud, carbide slag and industrial salt mud to form a gypsum-like substance containing calcium sulfate, which decomposes under heat to form sulfur-containing gas and form pores. The synergy of sulfuric acid slag, boron mud, carbide slag and industrial salt mud can improve the thermal insulation performance of ceramic materials.

[0011] In addition, industrial salt mud contains sodium salt, which reacts with raw materials to form sodium carbonate, and produces CO2 gas when heated. The above gas overflows and forms pores in the blocks, increasing the porosity and thus improving the thermal insulation effect of foam ceramic blocks.

[0012] Stress: The greater the stress, the closer the raw materials are, the denser the formed ceramic body is, and the higher the strength is. Therefore, the stress is selected between 15 and 20 MPa.

[0013] Preferably, the filler is at least one of pine nuts, castor beans, and Spartina alterniflora powder. The filler can increase the porosity and improve the thermal insulation performance, but has a negative impact on the strength, so the amount is controlled to be 5 to 10 parts.

[0014] The present invention also provides a method for preparing the foam ceramic building block, comprising the following steps:

[0015] S1. Dry and grind tap water tail mud, aluminum ash, flue ash and sulfuric acid slag to form a main material with a fineness of 100 to 300 meshes;

[0016] S2, drying and grinding at least one of the boron mud, carbide slag and industrial salt mud to form a pore-forming agent with a fineness of 50 to 100 mesh;

[0017] S3, washing at least one of pine nuts, castor seeds, and Spartina alterniflora powder, drying the powder naturally, and crushing the powder to form a filler having an average length of 1 to 3 mm;

[0018] S4, the obtained main material, pore-forming agent and filler are mixed evenly according to the designed proportion and loaded into a test mold, and a green body is formed through a stress of 15-20 MPa;

[0019] S5. calcining the prepared green body, raising the temperature to 1000-1500° C., keeping the temperature for 5-10 hours, and forming a foam ceramic building block through natural cooling.

[0020] The present invention further provides a method for using the foam ceramic building blocks, wherein the foam ceramic building blocks are bonded to each other by applying a masonry agent.

[0021] Preferably, the masonry agent comprises the following raw materials in parts by weight: 70-90 parts of plant extract, 10-30 parts of solid reinforcing agent, and 10-20 parts of industrial alcohol; the preparation method of the masonry agent is as follows: industrial alcohol is added to the plant extract to form a solution, and then mixed with the solid reinforcing agent to obtain the masonry agent.

[0022] In the above technical solution, industrial alcohol, plant extracts and solid reinforcing agents work together to ensure viscosity and strength while ensuring that the solidification time is not too fast, thereby improving the product quality of the masonry agent. Plant extracts produce lignin and cellulose adhesives, and solid reinforcing agents produce CSH gel, that is, hydrated calcium silicate gel. The ethanol in industrial alcohol can destroy the connecting bonds between the colloidal molecules produced by plant extracts and solid reinforcing agents, blocking molding. In addition, ethanol is more volatile and only plays a blocking role in a short period of time, which will not affect the later strength of the masonry agent, and industrial alcohol is cheap and low in cost.

[0023] Preferably, the plant extract comprises the following raw materials in parts by weight: 5-10 parts of ivy, 5-10 parts of oleander, 5-10 parts of buddleja, 20-30 parts of camphor leaves, 20-30 parts of paper mulberry leaves, and 20-25 parts of euphorbia pulcherrima.

[0024] Preferably, the preparation method of the plant extract is as follows: wash, dry, chop, mix evenly, add an equal amount of water and boil to prepare an extract.

[0025] Preferably, the solid enhancer comprises the following raw materials in parts by weight: 5-10 parts of phosphogypsum, 10-15 parts of quicklime, 35-55 parts of steel slag, and 20-50 parts of desulfurized ash.

[0026] Preferably, the preparation method of the solid reinforcing agent is as follows:

[0027] S1, drying and grinding the desulfurized ash and steel slag into a first powder of 50 to 100 mesh;

[0028] S2, drying and grinding the phosphogypsum and quicklime into a second powder of 100 to 200 meshes;

[0029] S3, mixing the first powder and the second powder evenly to form a solid reinforcing agent.

[0030] Compared with the prior art, the beneficial effects of the present invention are:

[0031] 1. The foam ceramic building block provided by the present invention uses tap water tail mud, aluminum ash, flue ash and sulfuric acid slag as main raw materials, at least one of boron mud, carbide slag and industrial salt mud as a pore-forming agent, and at least one of pine nuts, castor seeds and Spartina alterniflora powder as a filler. The foam ceramic building block has the characteristics of strong mechanical properties, good thermal insulation effect and excellent sound absorption ability, and has the basis for being used as an indoor partition material. The internal pore size of the foam ceramic building block is suitable and evenly distributed. The foam ceramic building block has a low preparation cost, and can be prepared into various specifications according to actual use needs. It is relatively convenient to use and has an industrialization basis. The present invention is of great significance in the fields of improving the comprehensive utilization rate of solid waste and developing energy-saving building materials.

[0032] 2. The masonry agent of the present invention uses plant extracts and industrial solid waste as basic raw materials, and has the advantages of low cost, simple process, non-toxic and environmentally friendly, and strong bonding, and is suitable for mass production. When using the high-performance masonry agent, it is only necessary to mix the extractant and the solid reinforcing agent evenly according to the designed proportion and apply it to the upper surface layer of the foam ceramic block with a thickness of 1 to 2 mm and press lightly. Compared with traditional masonry mortar and other materials, the high-performance masonry agent does not require the addition of aggregates, and has the advantages of low cost, environmental protection, non-toxicity, and stable performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a SEM picture of the interior of the foam ceramic in the embodiment of the present invention, showing an obvious honeycomb pore structure;

[0034] Figure 2 The X-ray diffraction patterns of different types of pore-forming agents after mixed reaction with raw materials in the embodiments of the present invention;

[0035] Figure 3 It is the XRD spectrum of the masonry agent in the embodiment of the present invention. DETAILED DESCRIPTION

[0036] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below with reference to specific diagrams.

[0037] Example 1

[0038] 50kg of tap water tail mud, 20kg of aluminum ash, 20kg of flue ash and 10kg of sulfuric acid slag are used as the main materials, and the fineness is 100 mesh. Boron mud with 100 mesh and castor bean powder with 1mm are used as pore-forming agent and filler, and the dosage is 10kg and 5kg respectively. The above main materials, pore-forming agent and filler are mixed evenly and formed into block blanks with a size of 240mm×115mm×53mm by 15MPa stress. After high-temperature calcination at 1000℃ and cooling for 5h, environmentally friendly foam ceramic blocks are prepared. The compressive strength, flexural strength, bulk density and thermal conductivity of the foam ceramic blocks are measured, and the results are shown in Table 1.

[0039] Example 2

[0040] 60kg of tap water tailings, 10kg of aluminum ash, 10kg of flue ash and 20kg of sulfuric acid slag are used as the main materials, with a fineness of 150 mesh. 50-mesh calcium carbide slag and 1mm pine nut powder are used as pore-forming agents and fillers, with an amount of 5kg and 5kg respectively. The above main materials, pore-forming agents and fillers are mixed evenly and a block blank with a size of 600mm×200mm×240mm is formed using a stress of 20MPa. After high-temperature calcination at 1300℃ and cooling for 10h, an environmentally friendly foam ceramic block is prepared. The compressive strength, flexural strength, bulk density and thermal conductivity of the foam ceramic block are measured, and the results are shown in Table 1.

[0041] Example 3

[0042] 40kg of tap water tail mud, 30kg of aluminum ash, 10kg of flue ash and 30kg of sulfuric acid slag are used as the main materials, with a fineness of 200 mesh. 100-mesh industrial salt mud and 1mm Spartina alterniflora leaf powder are used as pore-forming agent and filler, with an amount of 20kg and 10kg respectively. The above main materials, pore-forming agent and filler are mixed evenly and a block blank with a size of 240mm×115mm×53mm is formed using a stress of 15MPa. After high-temperature calcination at 1200℃ and cooling for 10h, an environmentally friendly foam ceramic block is prepared. The compressive strength, flexural strength, bulk density and thermal conductivity of the foam ceramic block are measured, and the results are shown in Table 1.

[0043] Example 4

[0044] 10kg of tap water tail mud, 30kg of aluminum ash, 30kg of flue ash and 10kg of sulfuric acid slag are used as the main materials, and the fineness is 300 mesh. 10kg of boron mud, 5kg of calcium carbide slag and 5kg of industrial salt mud are used as pore-forming agents, and the fineness is 100 mesh. 4kg of pine nuts, 3kg of castor beans and 3kg of Spartina alterniflora leaves are used as fillers to make 1-3mm crushed bodies. The above main materials, pore-forming agents and fillers are mixed evenly and 20MPa stress is used to form a block blank with a size of 600mm×200mm×240mm. After high-temperature calcination at 1500℃ and cooling for 5h, an environmentally friendly foam ceramic block is prepared. The compressive strength, flexural strength, bulk density, porosity and thermal conductivity of the foam ceramic block are measured, and the results are shown in Table 1.

[0045] Example 5

[0046] The difference between this embodiment and embodiment 4 is that no sulfuric acid slag is added.

[0047] Example 6

[0048] The difference between this embodiment and embodiment 1 is that no boron mud is added.

[0049] Example 7

[0050] The difference between this embodiment and embodiment 2 is that no carbide slag is added.

[0051] Example 8

[0052] The difference between this embodiment and embodiment 3 is that no industrial salt mud is added.

[0053] Example 9

[0054] The difference between this embodiment and embodiment 1 is that castor beans are not added.

[0055] Example 10

[0056] The difference between this embodiment and embodiment 2 is that no pine nut powder is added.

[0057] Embodiment 11

[0058] The difference between this embodiment and embodiment 3 is that no Spartina alterniflora leaf powder is added.

[0059] Comparative Example 1

[0060] Taking A10 autoclaved aerated concrete blocks with density grade B05 and size 600mm×200mm×240mm as the control group, the 28d compressive strength, flexural strength, bulk density, porosity and thermal conductivity were measured. The results are shown in Table 1.

[0061] Table 1 Statistics of performance parameters of various embodiments

[0062]

[0063] In combination with the above embodiments, the environmentally friendly foam ceramic block has a compressive strength of ≥78.00MPa, a flexural strength of ≥21.00MPa, and a bulk density of ≤260.00Kg / m 3 , porosity ≥ 80.00%, thermal conductivity ≤ 0.0170 W / (m·K). The foam ceramic block has excellent overall performance and is suitable for use as indoor partition wall materials.

[0064] In order to facilitate the normal use of the foam ceramic block, the present invention also provides a high-performance masonry agent and a preparation method. The performance of the masonry agent will be described in detail below in conjunction with a specific implementation case. For ease of understanding, a control group is set up in this implementation case, that is, traditional M5 and M7.5 masonry mortars are used for performance comparison, and the specific situation is as follows:

[0065] Example 12

[0066] 10kg of ivy, 10kg of oleander, 10kg of buddleja, 30kg of camphor leaves, 20kg of paper mulberry leaves and 20kg of euphorbia pulcherrima were washed and dried, then put into a boiling device and boiled with equal mass of clean water for 10 minutes to form an extract. 20kg of industrial alcohol was added to the extract to form a solution. 10kg of phosphogypsum, 15kg of quicklime, 35kg of steel slag and 40kg of desulfurized ash were dried and ground to prepare a solid enhancer with a fineness of 50-200 mesh, and a high-performance masonry agent was formed with a mass ratio of extractant: solid enhancer = 7:3. The initial viscosity, initial setting and final setting time and compressive strength of the masonry agent at different times were measured, and the relevant indicators were compared with the masonry mortars of M5.0 and M7.5. The results are shown in Table 2.

[0067] Example 13

[0068] Compared with Example 12, the proportion of plant materials in this embodiment is adjusted to 5kg of ivy, 10kg of oleander, 5kg of buddleja, 20kg of camphor leaves, 30kg of paper mulberry leaves, and 25kg of euphorbia pulcherrima, and the amount of industrial alcohol used is 10kg. The solid reinforcing agent is adjusted to 5kg of phosphogypsum, 10kg of quicklime, 55kg of steel slag, and 20kg of desulfurized ash. The ratio of extractant: solid reinforcing agent = 7kg: 3kg is used as a masonry agent. The initial viscosity, initial setting and final setting time, and compressive strength of the masonry agent at different time periods are measured. The relevant indicators are compared with the masonry mortars of M5.0 and M7.5. The results are shown in Table 2.

[0069] Embodiment 14

[0070] Compared with Example 12, the proportion of plant materials in this embodiment is adjusted to 10kg of ivy, 5kg of oleander, 10kg of buddleja, 25kg of camphor leaves, 25kg of paper mulberry leaves, and 25kg of euphorbia pulcherrima, and the amount of industrial alcohol used is 10kg. The solid reinforcing agent is adjusted to 5kg of phosphogypsum, 15kg of quicklime, 40kg of steel slag and 50kg of desulfurization ash mixed evenly to form a solid reinforcing agent. The ratio of extractant: solid reinforcing agent = 7kg: 1kg is used as a masonry agent, and the initial viscosity, initial setting and final setting time and compressive strength of the masonry agent at different time periods are measured. The relevant indicators are compared with the masonry mortars of M5.0 and M7.5. The results are shown in Table 2.

[0071] Embodiment 15

[0072] The difference between this embodiment and embodiment 14 is that the ratio of the extractant to the solid enhancer is adjusted to 9kg:1kg.

[0073] Example 16

[0074] The difference between this embodiment and embodiment 14 is that the ratio of the extractant to the solid enhancer is adjusted to 9kg:3kg.

[0075] Embodiment 17

[0076] Compared with Example 12, this embodiment differs in that no industrial alcohol is added.

[0077] Table 2 Statistics of main parameters of masonry agents

[0078]

[0079]

[0080] Combined with the data provided in each embodiment, the high-performance masonry agent meets the requirements of initial viscosity ≥ 62000cps, initial setting time ≥ 45min, and final setting time ≤ 350min. The 12h compressive strength is ≥ 2.33MPa, the 3d compressive strength is ≥ 3.90MPa, and the 28d compressive strength is ≥ 7.90MPa. The strength index is better than the requirements of M7.5 masonry mortar. The high-performance masonry agent does not require the use of aggregates, has the advantages of low cost, environmental protection, non-toxicity, and stable performance, and the high-performance masonry agent has an industrialization foundation.

[0081] Figure 2 The results show that the pore-forming agent boron mud contains Mg(OH)2 and MgSO4, which produce a large amount of water vapor, SO2 and O2 when heated; at the same time, the boron mud contains Ca(OH)2 and CaCO3, which react with SO4 in the sulfuric acid slag. 2-The reaction generates CaSO4, which decomposes when heated to produce a large amount of CO2, SO2 and O2, helping to form pores; on the other hand, the borax group contains BaSO4, which is easily decomposed when heated to generate SO2, thereby increasing the porosity of the foam ceramic.

[0082] The carbide slag component contains a large amount of Ca(OH)2 and CaCO3, which produce a large amount of water vapor and CO2 when thermally decomposed, thereby increasing the porosity of foam ceramics.

[0083] The industrial salt mud composition contains a large amount of CaCO3, Na2CO3 and NaHCO3, which produce a large amount of water vapor and CO2 when decomposed by heat, increasing the porosity of foam ceramics.

[0084] Figure 3 It is shown that the 12h and 3d compressive strengths of the masonry agent of the present invention are mainly achieved by the hydration reaction of phosphogypsum, quicklime and steel slag, and the gelling effect of lignin and cellulose adhesive in the plant extract. With the extension of age, the hydration reaction of steel slag is gradually improved. While forming a large amount of CSH gel, other alkaline substances produced by it continue to react with the active ingredients in the desulfurization ash to generate new aluminosilicate minerals, such as calcium sulfoxide, illite and orthorhombic zeolite, thereby forming new chemical bonding force.

[0085] The above are only implementation modes of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure made using the contents of the present invention's specification and drawings, directly or indirectly used in other related technical fields, are also within the patent protection scope of the present invention.

Claims

1. A foam ceramic block, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of main material, 5-20 parts of pore-forming agent, and 5-10 parts of filler. The main material comprises 10-70 parts of tap water tailings, 10-30 parts of aluminum ash, 10-30 parts of flue ash, and 10-30 parts of sulfuric acid slag. The pore-forming agent is at least one of boron mud, carbide slag and industrial salt mud. The filler is at least one of pine nuts, castor seeds, and Spartina alterniflora powder.

2. A method for preparing a foam ceramic building block as claimed in claim 1, characterized in that: The following steps are involved: S1. Dry and grind tap water tail mud, aluminum ash, flue ash and sulfuric acid slag to form a main material with a fineness of 100 to 300 meshes; S2, drying and grinding at least one of the boron mud, carbide slag and industrial salt mud to form a pore-forming agent with a fineness of 50 to 100 mesh; S3, washing at least one of pine nuts, castor seeds, and Spartina alterniflora powder, drying the powder naturally, and crushing the powder to form a filler having an average length of 1 to 3 mm; S4, the obtained main material, pore-forming agent and filler are mixed evenly according to the designed proportion and loaded into a test mold, and a green body is formed through a stress of 15-20 MPa; S5. calcining the green body, raising the temperature to 1000-1500° C., keeping the temperature for 5-10 hours, and forming a foam ceramic building block through natural cooling.

3. A method for using the foam ceramic building block according to claim 1, characterized in that: Foam ceramic blocks are bonded to each other using a smear of masonry agent.

4. The method of use according to claim 3, characterized in that: The masonry agent comprises the following raw materials in parts by weight: 70-90 parts of plant extract, 10-30 parts of solid reinforcing agent, and 10-20 parts of industrial alcohol; the preparation method of the masonry agent is as follows: industrial alcohol is added to the plant extract to form a solution, and then mixed with the solid reinforcing agent to obtain the masonry agent.

5. The method of use according to claim 4, characterized in that: The plant extract comprises the following raw materials in parts by weight: 5-10 parts of ivy, 5-10 parts of oleander, 5-10 parts of buddleja, 20-30 parts of camphor leaves, 20-30 parts of paper mulberry leaves, and 20-25 parts of euphorbia pulcherrima.

6. The method of use according to claim 5, characterized in that: The preparation method of the plant extract is as follows: wash, dry, chop, mix evenly, add an equal amount of water, boil, and prepare an extract.

7. The method of use according to claim 6, characterized in that: The solid reinforcing agent comprises the following raw materials in parts by weight: 5-10 parts of phosphogypsum, 10-15 parts of quicklime, 35-55 parts of steel slag, and 20-50 parts of desulfurized ash.

8. The method of use according to claim 7, characterized in that: The preparation method of the solid reinforcing agent is as follows: S1, drying and grinding the desulfurized ash and steel slag into a first powder of 50 to 100 mesh; S2, drying and grinding the phosphogypsum and quicklime into a second powder of 100 to 200 meshes; S3, mixing the first powder and the second powder evenly to form a solid reinforcing agent.

Citation Information

Patent Citations

  • Foam concrete block prepared from solid wastes and preparation method of foam concrete block

    CN113105195A